Development of Lactation Mobile Applications in Indonesia: A Systematic Literature Review - Rusmilawaty , Rusmilawaty; Sofia , Norlaila; Hapisah , Hapisah; Tunggal, Tri (Jurnal Teknokes, 2026)
Exclusive breastfeeding for six months is a critical public health intervention to reduce infant mortality in Indonesia. However, its implementation continues to face significant barriers, including low maternal health literacy, limited psychosocial support, and challenges in lactation management. Although digital health technologies have expanded rapidly, existing lactation applications in Indonesia remain fragmented and predominantly focus on one-way educational functions, without integrating maternal health data or clinical infant monitoring. This study aims to systematically analyze the characteristics and development trends of lactation mobile applications in Indonesia and to identify feature gaps, which will serve as the foundation for designing an integrated digital model. The main contribution of this study is the development of a conceptual framework for an integrated lactation technology model that combines breastfeeding education, family involvement, maternal factor documentation, and breast milk adequacy monitoring using infant physiological indicators, all within a single digital ecosystem. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines. Literature searches were performed using Publish or Perish software on the Google Scholar database for studies published between 2017 and February 2026 using structured keywords. Five eligible studies were analyzed thematically and appraised using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist. The review found that all identified applications were Android-based (100%, n=5). Four applications (80%) focused on maternal education and demonstrated improvements in knowledge and reduced anxiety; one (20%) emphasized family support through co-parenting; and one (20%) addressed lactation management via milk stock calculation features. No application integrates maternal history, early detection of lactation problems, and infant-based physiological monitoring within a unified platform. In conclusion, lactation application development in Indonesia remains fragmented and lacks a system-integrated approach. The proposed SiCubit conceptual model provides a decision-support framework for integrated breastfeeding monitoring and digital lactation support.